Protective Activity of Dendropanax Morbifera Against Cisplatin-Induced Acute Kidney Injury - Eun-Sun Kim; Jong Soo Lee; Muhammad Akram; Kyeong-A Kim; Young-Jun Shin; Jong-Hyun Yu; Ok-Nam Bae (Karger Publishers, 2015)
Background/Aims: Drug-induced acute kidney injury (AKI) has been a severe threat to hospitalized patients, raising the urgent needs to develop strategies to reduce AKI. We investigated the protective activity of Dendropanax morbifera (DP), a medicinal plant which has been widely used to treat infectious and pain diseases, on acute kidney injury (AKI) using cisplatin-induced nephropathic models. Methods: Both in vitro renal tubular cells (NRK-52E) and in vivo rat models were used to demonstrate the nephroprotective effect of DP. Results: Methanolic extract from DP significantly reduced cisplatin-induced toxicity in renal tubular cells. Through successive liquid extraction, the extract of DP was separated into n-hexane, CHCl3, EtOAc, n-BuOH, and H2O fractions. Among these, the CHCl3 fraction (DPCF) was found to be most potent. The protective activity of DPCF was found to be mediated through anti-oxidant, mitochondrial protective, and anti-apoptotic activities. In in vivo rat models of AKI, treatment with DPCF significantly reversed the cisplatin-induced increase in blood urea nitrogen and serum creatinine and histopathologic damage, recovered the level of anti-oxidant enzymes, and inhibited renal apoptosis. Conclusion: We demonstrated that DP extracts decreased cisplatin-induced renal toxicity, indicating its potential to ameliorate drug-associated acute kidney damage.